Dokumenter sebagai Alternatif Metode Konservasi untuk Nilai Budaya Kecamatan Andir - Utami, Lira Anindita; Lionardi, Angelia; Putri, Arum Githa; Apsari, Diani; Wiwaha, Luqman Rusdan (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2024)
Culture, as a multifaceted entity serves as a mirror reflecting how individuals interact with their surroundings and one another. Andir, a district located in Bandung Region of West Java, Indonesia with its rich tapestry of history and cultural diversity, demands a way to creatively preserve and showcase its cultural dynamic. By choosing documentary filmmaking as an instrument to record and safeguard the essence of cultural diversity of Andir, the authors gained a way to subjective and participatory exploration into the colorful scenes situated in Andir. Several techniques of immersion in the field such as walk-around and treasures mapping is employed in the filmmaking to construct a subjective experience and became a way of participatory learning of Andir’s culture for the people involved in this initiative. Documentary filmmaking emerges as an indispensable tool for recording and safeguarding the essence of Andir’s culture that allows for a more authentic portrayal of the cultural landscape. As a medium, it stands as a pivotal container of conservation through visual storytelling that amplifies the documentation and representation of cultural legacies for the next generation and for the audience. This study highlights the result of mapping the cultural dynamic that can be observed in socio-economic activities, culinary culture, and architecture. These are considered as the cultural assets in which the principles construct the cultural value of tolerance identified in Andir. It is then documented to construct the visual storytelling of documentary and to empower cultural conservation by creative media to raise awareness and foster future collaborative efforts. By showcasing the multifaceted cultural exchanges occurring within Andir in the visual storytelling, it offers a window into the cultural intricacies that define this community while becoming a medium that conserves the cultural scenery of everyday life. The film also captures the